Pelatihan Penulisan Karya Ilmiah Bagi Dosen Universitas Bale Bandung Sebagai Salah Satu Aksi Nyata Gerakan Nasional Revolusi Mental - Rina Andriani; Ibrahim Danuwikarsa; Emas Marlina (LPPM UNINUS, 2022)
The purpose of this program is as a first step to write scientific papers for lecturers at Bale University, Bandung, as one of the real actions of the national mental revolution movement which was carried out in collaboration with the Coordinating Ministry for Human Development and Culture and Bale Bandung University at Hotel Horison Bandung. The event was attended by the Chancellor of Bale Bandung University, Bandung Ibrahim Danuwikarsa, Deputy Coordinator for Mental Revolution, Promotion of Culture and Sports Achievement at the Coordinating Ministry for Human Development and Culture, Didik Suhardi, Professor at Padjadjaran University, Bandung Prof. Reginawati Hidersah and the Research and Community Service Institute Team at Bale Bandung University along with dozens lecturer. The implementation method is 1). training in writing scientific papers for lecturers at Bale University, Bandung; 2) Assistance in writing scientific papers for lecturers; 3). Publication of scientific journals produced by lecturers at Bale University, Bandung.